Academics at three African universities on the perceived utilisation of their research - Boshoff, N.; Esterhuyse, H.; Wachira-Mbui, D.N.; Owoaje, E.T.; Nyandwi, T.; Mutarindwa, S. (South African Journal of Higher Education, 2019)
This article contributes to emerging knowledge on the utilisation of university research in sub-Saharan Africa. A survey was conducted comprising 463 academics at three African universities: the University of Ibadan (Nigeria), the University of Nairobi (Kenya) and the University of Rwanda. The study investigated the agreement between two measures of research utilisation and highlighted the types of research interactions associated with instances of perceived research utilisation, whilst taking into account the different categories of intended beneficiaries. The first measure, a single question, required the respondents to indicate to what extent the stated intended beneficiaries had utilised the research as planned. The second measure operationalised a stage model of research utilisation. Responses at the ‘upper end’ of both measures were labelled ‘true’ research utilisation. A percentage reduction in utilisation was observed when cross-tabulating the two measures – from 48 per cent who believed that research utilisation occurred to some extent (upper end of first measure), to 35 per cent who held the same opinion and who obtained above-average scores on the stage model of utilisation (upper end of second measure). For the subgroup at the upper end of both measures, the larger share of cases (54%) exemplified the instrumental utilisation of research. This subgroup was found to be involved in traditional academic research practices and participated in a number of outreach activities targeting non-academic audiences.